2007
DOI: 10.1086/520322
|View full text |Cite
|
Sign up to set email alerts
|

The Weak Absorbing Outflow in AGN Mrk 279: Evidence of Supersolar Metal Abundances

Abstract: We present analysis and photoionization modeling of the Chandra high-resolution spectrum of Mrk 279. There is clear evidence of an absorbing outflow that is best fit by a two-component model: one with a low-ionization parameter and one with a higher ionization parameter. The column density of the X-ray warm absorber, about log N H ¼ 20, is the smallest known of all active galactic nuclei (AGNs) in which X-ray absorbing outflows are observed. We find that the X-ray and UV/ FUV absorbers are part of the same ove… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 35 publications
(75 reference statements)
2
30
2
Order By: Relevance
“…values in quasars, Groves et al (2006) found that the narrow line regions had Z/Z ! ~2 -4, and Fields et al (2007) find evidence for Z/Z ! > 2 in a WA.…”
Section: Theoreticalmentioning
confidence: 98%
“…values in quasars, Groves et al (2006) found that the narrow line regions had Z/Z ! ~2 -4, and Fields et al (2007) find evidence for Z/Z ! > 2 in a WA.…”
Section: Theoreticalmentioning
confidence: 98%
“…However, Fields et al (2007) found evidence for the presence of different layers of highly ionized absorbing material from the spectral analysis of the soft X-ray Chandra LETG data. The associated column densities are low, of the order of N H ∼ 10 20 cm −2 , and the outflow velocities are of few ∼1000 km s −1 .…”
Section: Appendix B: Notes On Single Sourcesmentioning
confidence: 99%
“…These lines also appear to be observed in the RGS (Smith et al 2008) and the HETGS (Matsumoto et al 2004) spectra of Ark 564. If the ionized gas has solar abundances, oxygen absorption features are expected and have been detected in several AGNs with warm absorbers (e.g., Kaastra et al 2000;Sako et al 2001;Lee et al 2001;Blustin et al 2003;Krongold et al 2003;Netzer et al 2003;Fields et al 2007;Costantini et al 2007;Krongold et al 2007). However, only a few of them have well-measured column densities.…”
Section: High-resolution Spectral Analysismentioning
confidence: 99%